Evaluation of Implementation of Post-Transition Management Post Report by Provincial Government: (Case Study at State Senior High School 19 and State Senior High School 20 Surabaya) - Roekminiati, Sri; Astuti, Chistiana; Kamariyah, Sri (Asketik: Jurnal Agama dan Perubahan Sosial, 2018)
Precisely As of January 2017, Senior High School / Senior Vocational School officially managed the province. Naming Online Reports become an e-report card. Online report cards can be accessed by guardians and students wherever located. While the online report card still can not be accessed publicly. Accessible only by teacher, admin/operator. Match Evaluation Research Results: The e-Rapor Policy is appropriate and feasible to maintain. The e-Rapor policy does not require a new policy as a replacement. Evaluation of Effectiveness: Facilitate the incorporation of scores, chart student scores and also counseling guidance and connect with DAPODIK Center. Service Performance B or Satisfactory, Evaluation Efficiency: Input issued with the output/output of e-report cards is comparable. The effect of e-Rapor is efficient. Meta Evaluation: This e-Rapor evaluation is performed by Provincial School Trustees professionally per semester Evaluation result e - Reports into school considerations in taking the policy. Factors That Become Constraints: The e-Rapor application often updates the system. Have not yet adjusted the e-Rapor Application with the revised 2013 curriculum. Technically e-Rapor application is classified as a heavy application.4) Limit Description KIKD 60 characters. Suggestions and recommendations: For School Parties: Continue to upgrade the server and speed to increase e-Rapor access. For Kemendikbud: The application of e-Rapor is technically not heavy. 3) No Limitations of 60 characters for KIKD description. In the future, e-Rapor can be accessed by parents.